Early thrombosis prophylaxis with enoxaparin is not associated with hematoma expansion in patients with spontaneous intracerebral hemorrhage. (6th December 2018) - Ianosi, B.; Gaasch, M.; Rass, V.; Huber, L.; Hackl, W.; Kofler, M.; Schiefecker, A. J.; Addis, A.; Beer, R.; Rhomberg, P.; Pfausler, B.; Thomé, C.; et al.
Abstract : Background and purpose: Early pharmacological deep vein thrombosis (DVT) prophylaxis is recommended by guidelines, but rarely started within 48 h. We aimed to analyze the effect of early (within 48 h) versus late (>48 h) DVT prophylaxis on hematoma expansion (HE) and outcome in patients with spontaneous intracerebral hemorrhage (ICH). Methods: We analyzed 134 consecutive patients admitted to a tertiary neurointensive care unit with diagnosed spontaneous ICH, without previous anticoagulation, severe coagulopathy, hematoma evacuation, early withdrawal of therapy or ineligibility for DVT prophylaxis according to our institutional protocol. Significant late HE was defined as ≥6 mL increase of hematoma volume between neuroimaging within 48 h and day 3–6. Multivariate analysis was performed to identify risk factors for late HE, poor 3‐month outcome (modified Rankin Scale score ≥ 4) and mortality. Results: Patients had a median Glasgow Coma Scale score of 14 [interquartile range (IQR), 10–15], ICH volume of 11 (IQR, 5–24) mL and were 71 (IQR, 61–76) years old. A total of 56% ( n = 76) received early DVT prophylaxis, 37% ( n = 50) received late DVT prophylaxis and 8 (6%) had unknown bleeding onset. Patients with early DVT prophylaxis had smaller ICH volume [9.5 (IQR, 4–18.5) vs. 17.5 (IQR, 8–29) mL, P = 0.038] and were more often comatose (26% vs. 10%, P = 0.025). Significant late HE [ n = 5/134 (3.7%)] was associated with larger initial ICH volume ( P = 0.02) and lower thrombocyte count ( P = 0.03) but not with early DVT prophylaxis ( P = 0.36). Early DVT prophylaxis was not associated with worse outcome. Conclusion: Significant late HE is uncommon and DVT prophylaxis within 48 h of symptom onset may be safe in selected patients with ICH.